2020
DOI: 10.1109/access.2020.3021185
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SDN-Based Application-Awareness Mechanism by Using Deep Learning

Abstract: With the rapid development of the Internet of Things (IoT) and smart cities, more and more types of applications have been emerging. In fact, different applications have different features and different requirements on services. In order to satisfy users' Quality of Service (QoS) requirements, the application-awareness technique should be leveraged to distinguish different applications for providing the differentiated services. However, the traditional Internet only can obtain the local network view, which bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This section makes simulations based on SDICN network structure and CNN training model. At first, the experimental results on CNN training are shown in Table 1, including recall ratio, precision ratio and F1 value 9 …”
Section: Simulation Resultsmentioning
confidence: 99%
“…This section makes simulations based on SDICN network structure and CNN training model. At first, the experimental results on CNN training are shown in Table 1, including recall ratio, precision ratio and F1 value 9 …”
Section: Simulation Resultsmentioning
confidence: 99%
“…The recall ratio, precision ration and F1 value are shown in Table 1, where the definitions of three metrics can be found from Reference 10. It is observed that, the adopted DBN neural network structure in this letter has the highest recall ratio, precision ratio and F1 value, which indicates that DBN has the best psychology recognition effect in terms of the collected psychology data of 4000 undergraduates.…”
Section: Simulationsmentioning
confidence: 86%
“…The comparative analysis against the individual single classifier and voting ensemble demonstrates the effectiveness of the proposed ensemble. As DL helps to eliminate the manual feature engineering task, Hu et al [83] proposed a CNN-based deep learning method to address the SDN-based application awareness called CDSA. As shown in Figure 6, CDSA consists of three components, which are traffic collection, data pre-processing, and application awareness.…”
Section: Coarse-grained Traffic Classificationmentioning
confidence: 99%